Penerapan Permainan Meniru Kata Untuk Meningkatkan Kemampuan Menulis Nama Sendiri Pada Anak Kelompok B di TK GMIM Siloam Tara-Tara - Lengkong, Eduard Jeconya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was motivated by the situation where group B children at the GMIM Siloam Taratara Kindergarten still did not make enough scribbles on paper or other media prepared by the teacher so that the children were unable to write their own names. Researchers apply word imitation games to improve children's ability to write their own names. Writing this thesis uses the Kemmis and Mc model of Classroom Action Research (PTK) approach. Taggart with steps starting from planning, implementation, observation and reflection which are carried out in two cycles. The research subjects were 20 people, consisting of 12 men and 8 women. Data collection techniques are carried out through observation and tests. The results showed that in cycle I it was 70% and cycle II it was 83.75%. The conclusion of this research is that implementing word imitation games can improve children's ability to write their own names. So it is recommended for kindergarten children to be more active in learning activities that apply word imitation games, kindergarten teachers to use word imitation games to stimulate children's ability to write their own names, and for the school to always provide support and be open to implementing word imitation games in learning process.